1992
DOI: 10.1159/000175015
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Related to the 7-Year Prognosis for Patients Suspected of Myocardial Infarction with and without Confirmed Diagnosis

Abstract: This study prospectively evaluates the long-term prognosis of patients admitted with chest pain under suspicion of acute myocardial infarction (AMI) with and without confirmed diagnosis. All patients below 76 years of age, free of other severe diseases and alive at discharge, who were admitted to a coronary care unit of a well-defined region during 1 year, constituted the study population. In all, 275 patients with and 257 patients without confirmed AMI (non-AMI) were included. During 7 years of follow-up, 122… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 13 publications
(27 reference statements)
2
10
0
Order By: Relevance
“…The risk factors for AMI patients, age, pre vious AMI, clinical heart failure and diabetes, correspond to previous findings [ 10,15]. In this study with a large study population, a history of angina pectoris was shown to contain indepen dent prognostic information too (table 2).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The risk factors for AMI patients, age, pre vious AMI, clinical heart failure and diabetes, correspond to previous findings [ 10,15]. In this study with a large study population, a history of angina pectoris was shown to contain indepen dent prognostic information too (table 2).…”
Section: Discussionsupporting
confidence: 89%
“…How ever, the study suggested that the prognosis of non-AMI patients was very similar to that of patients with AMI. Now it is well documented that both the short-and the long-term prog noses are impaired among the subset of non-AMI patients who have coronary artery dis ease [4,5,10,11,19], whereas patients with out signs of coronary artery disease at exercise test or thallium scintigraphy have an excellent long-term prognosis [24,25], Consequently, all non-AMI patients should now undergo careful evaluation regarding coronary artery disease at the time of discharge in order to be able to optimize the risk stratification, treat ment and follow-up of high-risk patients. 265 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, risk stratification was not per formed. and we recently reported that both a history of angina pectoris and ST-T changes in the ECG on admission contained indepen dent prognostic information on long-term prognosis [14], Only few of the patients with noncoronary chest pain had a history of angina pectoris (8%) or previous AMI (7%). In spite of this, the cardiac mortality was almost twice as high as in the patients with coronary chest pain (32 vs. 17%).…”
Section: Discussionmentioning
confidence: 97%
“…The cardiac event rate is almost as high as in patients with confirmed infarction (AMI) and significantly higher than in the background population for up to 10 years after discharge [5,6], The short-and long-term risk has been shown to be KARGER closely associated with signs of ischemic heart disease (IHD) identified from the medical history [2,6], the ECG on admission [2,6. 7] or from an exercise test and/or myo cardial scintigraphy [7.…”
Section: Introductionmentioning
confidence: 99%